Mobilizing sorghum genetic diversity: Biochemical and histological‐assisted design of a stem ideotype for biomethane production. Issue 12 (25th September 2021) - Thomas, Hélène Laurence; Pot, David; Jaffuel, Sylvie; Verdeil, Jean‐Luc; Baptiste, Christelle; Bonnal, Laurent; Trouche, Gilles; Bastianelli, Denis; Latrille, Eric; Berger, Angélique; Calatayud, Caroline; Chauvergne, Céline; et al.
Abstract: Sorghum currently contributes to the species portfolio that is supporting bioenergy production including anaerobic digestion. Although agro‐morphological ideotypes maximizing biogas production have been recently proposed, there is a crucial need to refine our understanding of the impacts of the stem composition and structure on this processing trait in order to ensure genetic gains in the mid to long terms. This study aims to assess the potential of Sorghum bicolor ssp bicolor stem genetic diversity to maximize genetic gains for biogas production and define a biogas stem ideotype. In this context, a panel of 57 genotypes, encompassing most of the stem composition variability available in cultivated sorghum, was characterized over five sites. Simultaneous histological and biochemical characterizations were performed. A high broad sense heritability associated with a moderate genetic variability was detected for stem biogas potential ensuring significant genetic gains in the future. In addition, the development of a stem histological phenotyping pipeline made it possible to describe the genetic diversity available for the internode anatomy and the repartition of key cell wall components. Consistently with previous studies, moderate to high heritability was observed for stem biochemical components. Genetic correlation, hierarchical clustering, and multiple stepwise regression analyses identified soluble sugar content as the first main driver of biogas potential genetic variability. Nevertheless, breeding programs should anticipate that biogas yield improvement will also rely on the monitoring of the cell wall components and their distribution in the stem jointly with the soluble sugar content. According to the assets of sorghum in terms of adaptation to environmental stresses and the present results regarding the identification of stem ideotypes suitable for different value chains, this species will surely play a key role to optimize the economic and environmental sustainability of the agrosystems that are currently facing the effects of climate change. Abstract : Sorghum currently contributes to the species portfolio that is supporting bioenergy production including anaerobic digestion. Although agro‐morphological ideotypes maximizing biogas production have been recently proposed, there is a crucial need to refine our understanding of the impacts of the stem composition and structure on this processing trait in order to ensure genetic gains in the mid to long terms. Combining biochemical, histological and processing traits characterizations, a sorghum stem ideotype maximizing biogas production was identified and compared with the ones corresponding to the animal feed and combustion value chains.